Bridging Policy and Practice: Evaluating the Implementation of Disaster Response Technologies in Central Sulawesi, Indonesia - Fery Fery; Muhamad Dasril (Lembaga Bale Literasi, 2026)
This study explores the implementation of digital applications in disaster emergency response by the Regional Disaster Management Agency (BPBD) of Central Sulawesi, as mandated by Indonesia’s national disaster management policy. The research evaluates three main applications—Desk Relawan, Web GIS, and Pusdalops—to assess their effectiveness, identify implementation barriers, and determine alignment with policy frameworks. Using a qualitative descriptive method, data were collected through interviews, observations, and document analysis, with purposive sampling to select informants involved in system deployment. Thematic analysis was conducted using Charles O. Jones’ policy implementation model. Findings reveal that while BPBD has adopted digital tools in line with policy, application performance varied. Desk Relawan, aimed at volunteer coordination, was hindered by usability and access issues. Web GIS contributed to spatial analysis but was limited by poor infrastructure in remote areas. Pusdalops emerged as the most functional, offering real-time information sharing, though lacking system integration reduced its overall impact. Key challenges include limited organizational capacity, infrastructure gaps, and weak inter-agency coordination. These obstacles suggest that effective IT integration in disaster response requires not only technological adoption but also institutional preparedness, ongoing training, participatory system design, and collaborative governance. This study contributes to the literature on digital disaster management by providing context-specific insights from a decentralized setting. It emphasizes the need for targeted policy refinement and strategic investment to enhance digital transformation in regional disaster management.